Working time, inequality and carbon emissions in the United States: A multi-dividend approach to climate change mitigation. (February 2022) - Fitzgerald, Jared Berry
Abstract: Moving beyond mainstream approaches to climate change mitigation that focus primarily on technological advancements, proponents of a working time reduction argue that it is a multi-dividend sustainability policy that can simultaneously reduce environmental pressures while improving other social and economic outcomes. While research in this area generally finds significant positive associations between working hours and various environmental outcomes, one question that remains unexamined is how other structural factors might shape this relationship. This study advances research on the environmental consequences of working hours by considering how inequality moderates the relationship between average working hours and CO2 emissions across US states from 2005 to 2015. Integrating arguments from literatures on the environmental consequences of inequality and working hours, I propose that inequality amplifies the effects of working hours on emissions by increasing the overall scale of consumption and shaping the composition of that consumption to be more environmentally intensive. Results of two-way fixed-effects regression models provide support for this proposition. The findings indicate that the effects of average working hours on emissions increase in magnitude at higher levels of inequality. This study advances the understanding of the mechanisms behind working time and inequality that shape emissions. The findings also suggest that policies aimed at reducing inequality while simultaneously reducing pressures for longer working hours are likely to be socially and ecologically beneficial while also potentially mitigating the possibility of rebound effects.